The case against intergenerational accounting: The accounting campaign against social security and Medicare - James K. Galbraith; L. Randall Wray; Warren Mosler (Levy Economics Institute of Bard College, 2009)
The Federal Accounting Standards Advisory Board (FASAB) has proposed subjecting the entire federal budget to intergenerational accounting - which purports to calculate the debt burden our generation will leave for future generations - and is soliciting comments on the recommendations of its two exposure drafts. The authors of this brief find that intergenerational accounting is a deeply flawed and unsound concept that should play no role in federal government budgeting, and that arguments based on this concept do not support a case for cutting Social Security or Medicare. The FASAB exposure drafts have not made a persuasive argument about basic matters of accounting, say the authors. Federal budget accounting should not follow the same procedures adopted by households or business firms because the government operates in the public interest, with the power to tax and issue money. There is no evidence, nor any economic theory, behind the proposition that government spending needs to match receipts. Social Security and Medicare spending need not be politically constrained by tax receipts - there cannot be any underfunding. What matters is the overall fiscal stance of the government, not the stance attributed to one part of the budget.
Keywords: 330